Duration of one unit (80 kcal) during treadmill walking - Onoi, K.; Nishimural, K.; Onodera, S. (Biomechanics and Medicine in Swimming X, 2006)
The number of Japanese people diagnosed with diabetes has been increasing. Epidemiological and intervention studies of endurance exercise training strongly support its efficacy for improving diabetes. The purpose of the present study was to make clear the difference of duration per expended one unit (80kcal) during treadmill walking in water between younger and older people. We would get the standard data by using non diabetes people. Ten healthy young men and eight healthy women participated in this study. Subjects walked at 1, 2 and 3km/h (30.3°C). The duration of exercise that expended one unit of energy was calculated from V02. Younger and older people's calculated results were 41'39" and 39'44" (I km/h), 33'22" and 31'56" (2km/h) and 24'51" and 24'56" (3km/h). There was no difference due to the difference of the age in one unit. It might be suggested that it becomes possible to prescribe underwater exercise for older diabetes patients by using the young's one unit index.